Membrane permeation properties of benzo[a]phenoxazinium fluorescent probes using molecular modelling techniques - Micaelo, N. M. (2011)
Studies of membrane permeation properties of four benzo[a]phenoxazinium fluorescent probes with twenty carbon atoms at the 5- or 9-positions of the tetracyclic ring in 2,3-bis(palmitoyl-oxy)propyl-2-(trimethylammonio)ethyl phosphate, DPPC membranes using molecular modelling techniques were carried out. The molecular mechanism of interaction between the molecular probes and the DPPC lipids is described. It was showed that probes can be preferentially located at the membrane water interface interaction with the lipid polar groups, while others can be cross the membrane in a passive way. This processes is dependent on the tetracyclic substitutions and the alkyl chains present in the fluorescent probe. These findings can provide a detailed rational of the structural properties surrounding the molecular probes that could be correlated with the experimentally measured fluorescence.